The status of China’s international division of labour from Marx’s theory of international value - Hui Ouyang; Huaibing Chen; Johnny Fat Iam Lam; Xianke Li (PLoS ONE, 2025)
Based on Marx’s theory of international value, this paper analyzes the carrier of unequal exchange and the path of international transfer of surplus value, constructs an international division of labour status index by comprehensively observing the organic composition of capital in the export and import sectors, and tries to accurately grasp the characteristics of the current international division of labour pattern coexisting between horizontal products and vertical products. At the same time, based on the data of all available HS92 six-digit code categories in various countries in the world from 1993 to 2016, the level of international division of labour in China is empirically analysed. The results show that: (1) there is no breakthrough in the situation of China’s low status of international division of labour; (2) the high capital-organic composition of the import sector is the main reason for the low status of international division of labour; (3) the continuous decline in the absolute value of captured surplus is a global phenomenon; (4) WTO accession has not significantly improved the status of international division of labour. Finally, the idea of improving the status of international division of labour through the development of domestic regional cooperation is put forward.